Longitudinal blood gas profiling reveals relative systemic hypoxia and its consequences for health and production in transition dairy cows - Fangchao Wu; Feixiang Fan; Zhiyao Guo; Haoyu Che; Zihai Wei; Hong-Yun Liu; Hui-Zeng Sun; Jian-Xin Liu; Feng-Fei Gu (Animal Bioscience, 2026)
Objective: This study aimed to investigate whether transition dairy cows experience a negative oxygen balance due to increased metabolic demands postpartum and to assess how this imbalance affects their health and production performance. The goal was to elucidate the longitudinal changes in blood gas parameters and establish links between hypoxic stress and physiological, inflammatory, and productive indicators.Methods: Ninety Holstein cows were monitored from 21 days before to 49 days after calving, with blood gas parameters, plasma biochemical indices, dry matter intake, and milk production being recorded at multiple time points. To assess the impact of hypoxia, cows were further grouped by postpartum hypoxia-inducible factor 1α (HIF-1α) levels into high and low hypoxic stress groups for comparative analysis.Results: During the transition period, dairy cows exhibited a significant postpartum reduction in arterial and venous hemoglobin (Hb), hematocrit (HCT), and oxygen concentration, reaching the lowest levels at 21 days after calving, while CO2-related parameters like TCO2, HCO3–, and BEecf increased. Cows with higher HIF-1α levels (HHS group) showed decreased dry matter intake and milk fat concentration, along with higher plasma β-hydroxybutyrate, malondialdehyde, and haptoglobin levels. Furthermore, significant correlations were observed between blood gas indicators and health parameters, including a negative correlation of SAA with Hb and HCT, highlighting the link between impaired oxygen transport and systemic stress responses.Conclusion: Postpartum dairy cows characterized by decreased oxygen delivery (lower Hb and HCT) and increased oxygen consumption (elevated CO2-related parameters), leading to relative metabolic systemic hypoxic stress. This imbalance is associated with liver stress, inflammation, oxidative damage, and reduced feed intake and milk production. These findings underscore the critical need for nutritional and management strategies targeting oxygen availability to support health and productivity during the transition period.